(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The "Heart Attack Risk Prediction using Retinal Eye Images" project presents a novel approach to cardiovascular health assessment by leveraging advanced image processing techniques. This innovative methodology focuses on the analysis of retinal images to infer potential indicators of heart attack risk.